Kedudukan Anak Perempuan dalam Warisan Menurut Kompilasi Hukum Islam dan Budaya Batak Toba Studi Kasus di Kecamatan Pangaribuan Kabupaten Tapanuli Utara - Siregar, Ermina Oktaviana; Marpaung, Arifin; Hayati, Amal (AHKAM, 2023)
The problem of inheritance is a discussion that has been discussed clearly and in detail in the Al-Qur'an and Sunnah on how to resolve it. However, along with developments over time, there are bound to be problems that arise in resolving inheritance issues among society. Not only in this day and age, even during the time of the Prophet SAW there were often disputes between his heirs. This thesis discusses the Position of Girls in Inheritance According to the Compilation of Islamic Law and Toba Batak Culture, where the Toba Batak Culture says that girls are not heirs. The method used is empirical juridical, which uses empirical facts that examine applicable legal provisions and what happens in reality in society. The nature of the research used is descriptive, where research only describes the situation of facts or incident. Based on the research results, the application of Islamic inheritance law in the Toba Batak Community in Pangaribuan sub-district, North Tapanuli district has not used Islamic law as its inheritance law, but still uses customary law. Toba Batak heirs in Pangaribuan sub-district, North Tapanuli regency usually hold deliberations to resolve this either only with their families or with traditional elders.